FOREIGN POLICY STRATEGIES FOR ENHANCING THE INDIAN ECONOMY: AN ANALYSIS (International Journal of Food and Nutritional Sciences, 2022)
Foreign policy strategies play a crucial role in determining a country’s economic growth and development. This research paper aims to analyze the impact of foreign policy on the Indian economy and proposes effective strategies that can be implemented to boost economic growth. The paper highlights the importance of trade, investment and technological advancements in strengthening in economy and argues that foreign policy can play a significant role in achieving these objectives.